PENGARUH DIKLAT, DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI BALAI DIKLAT KEAGAMAAN AMBON - La Edy; Agustina Risambessy (Soso-Q : Jurnal Manajemen, 2018)
The Effect of Education and Raining, Work Discipline and Compentency on the Employees’ Performance of Religious Education Center Ambon.This study aimed at finding out the effect of education and training on employees’ performance, finding out the effect of competency on employees’ performance.This study was a census research due to the population and samples in this study were the whole employees’ at Religious Education Center amounting for 43 people. The analysis method used in this study was descriptive analysis.Based on the results, it was found that there was a positive and significant effect of education and training on eployees’ performance; there was a positive    and significant effect of work discipline on employees’ performance and finding; there was a positive and significant effect of competency on employees’ performance. These results reveal that all hypoteheses were accepted.Keywords: education and training, disicipline, competence and performcance